Determination of oil contents from eight varieties of olea europaea (Olive) grown in Pakistan. Issue 13 (2nd July 2020) - Khaliq, Abdul; Ali Shah, Syed Muhammad; Akram, Muhammad; Munir, Naveed; Daniyal, Muhammad; Irshad, Muhammad; Ahmad, Saeed
Abstract: The olive ( Olea europaea L.) is a worldwide famous tree crop having valuable commercial role due to nutritional as well as therapeutic benefits obtained from its edible oil. Eight varieties of Olea europaea L. fruits were obtained from three Agricultural research institutes located in different areas of Pakistan including Quetta, Lorallia and Zhob to extract and determine their oil contents by conventional method as solvent extraction (soxhlet apparatus). Statistical analysis showed significant ( p = 0.002) difference in oil composition of collected plants. Highest amount (percentage) of oil was obtained from Gemlik variety (65%) from Lorallia and lowest oil content from Dolece-agogia variety (17.5%) collected from Quetta. Further research is under consideration to rule out best suitable factors including some soil and environmental factors to obtained more potential cultivars of Olea europaea in Pakistan. Abstract: